Local press as a public ombudsman - Lacerda, Rosa Mirah Araújo Gomes (Organicom, 2010)
New technologies have disseminated access to information, broadening the public’s independence. In this context, the local press looks at the community demands and assumes the role of a mediator between the population’s problems and the governmental bodies. The local news acts as an informal public ombudsman, focusing on cases that involve the government and using exposure and embarrassment as efficient tools for the quest for solutions.